The impact of media pressure on corporate sustainability in the cement industry: a Portuguese case study - Eugénio, T. P.; Lourenço, I. C.; Morais, A. I.; Branco, M. C. (Caspian Journal of Applied Sciences Research, 2015)
In this study we examine the sustainability reporting practices and sustainability strategies of a leading Portuguese cement company. The Portuguese cement industry had to deal since 1997 with scrutiny and pressure because of its involvement in co-incineration of hazardous industrial waste. Grounded on a lens of analysis combining legitimacy theory and media agenda-setting theory and based on a content analysis of sustainability reports and semi-structured interviews, we analyse the strategies used by the company to deal with said scrutiny and pressure and present its sustainability performance. Media pressure does seem to have impacted sustainability reporting and sustainability strategies as tools for the company to restore its legitimacy. Findings generally suggest that strategies of communication designed to legitimate the company actions were used. In particular, we suggest that the company managed its legitimacy by using simultaneously two sustainability reporting strategies: one of image enhancement and other of avoidance of threatening topics.